An Investigation on Three-Point Bending of Foam-Filled Double Tubes and Parameter Optimization Using Response Surface Methodology - Abdolvahed Kami; Javad Shahbazi Karami (Mechanics of Advanced Composite Structures)
The bending behavior of foam-filled double (FFD) tubes was studied in this study. The goal was to create an optimal structure that could absorb the most energy while weighing the least. On aluminum FFD tubes composed of inner and outer tubes (1100 aluminum alloy) and a composite foam core (with A356 cast alloy base and 0.6 g/cm3 density), three-point bending tests were conducted. Additionally, a finite element model of tube bending was developed and its outputs were validated using experimental data. Following that, the response surface methodology (RSM) was used to (numerically) investigate the influence of inner and outer tube diameters, inner and outer tube thickness, and foam density on bending energy and weight of FFD tubes. The impact of the investigated factors was investigated using analysis of variance (ANOVA). Finally, RSM was used to compute the best values of the parameters that result in the maximum energy absorption in bending and the lightest weight of the FFD tube. The optimization process resulted in a 141.4% increase in absorbed bending energy and a 4.63% reduction in the FFD composite tube's weight (in comparison to the initial design of the FFD tube).